MENINGITIS TUBERCULOSIS - Silvia Rachmayati; Ida Parwati; A Rizal; D Oktavia (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Tuberculosis meningitis is one of the clinical manifestations of extra-pulmonary TB, which is localized in the central nervous system(CNS). The mortality of these patients is usually caused by the delays in diagnosis and treatment; hence up to this day tuberculosismeningitis remains a health problem. The diagnosis of tuberculosis meningitis based on the discovery of M.tuberculosis established inthe cerebrospinal fluid (CSF) and is the gold standard by culture, although the examination results will be obtained after 6–8 weeks.Nevertheless the patient in this case needs an immediate and accurate treatment. Recently there is a rapid and accurate test to confirmthe diagnosis of tuberculosis meningitis, that is the detection of an immunoglobulin (Ig) M and G in the serum. The aim of this study isto know the validity and the correlation of IgG and IgM test to the gold standard by investigated them. The research is an observationalstudy conducted cross sectional in the Clinical Pathology Department of Hasan Sadikin Hospital, from October 2008 up to January 2009.Eighty samples were obtained, which included the criteria for patients with suspected tuberculosis meningitis. The result of this studyshows: sensitivity 94.1%, specificity 100%, positive predictive value 100%, negative predictive value 95.8%, positive infinite likelihoodratio (LHR), negative LHR 0.06 and kappa 0.95. According to this study it can be concluded, that the IgM/IgG TB is a test that has anexcellent validity and correlation for the future.